SVT news 2005 - Språkbanken Text (University of Gothenburg, 2024)
News texts from svt.se

Nyhetstexter från svt.se
SVT nyheter 2005
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik